Effects of oil price fluctuations on government expenditures, manufacturing output and trade balance in Saudi Arabia, Kuwait and United Arab Emirates - Faheem, Muhammad (2020)
This study analyzed the effect of oil price fluctuations on government expenditures, manufacturing output and trade balance in Saudi Arabia, Kuwait and United Arab Emirates. The time series linear autoregressive distributed model (ARDL) and nonlinear autoregressive distributed model (NARDL) were used to test the short-run and long-run effects of oil price on government expenditures, manufacturing output and trade balance. The first objective of this study is to analyze the effect of oil price fluctuations on government expenditures over the period of 1991-2017. The results of linear ARDL model found that oil price, real effective exchange rate, real GDP and government revenue positively affected government expenditures. The linear ARDL model is an insufficient capability for the detection of asymmetric behavior of oil price so, this study further estimated the non-linear model by decomposing oil price into positive and negative changes. The results of non-linear model showed that positive oil price changes encourage and negative oil price discourage government expenditures, but this impact is higher in case of oil price decrease in these countries except United Arab Emirates. Furthermore, the causal relationship of real GDP to government spending shows the evidence of the Wagner’s law is observed in the case of Saudi Arabia. While Kuwait fits both theories at a time and existence of Keynesian hypothesis confirms only in United Arab Emirates. Moreover, the results show strong causality running from government spending to government revenue in Saudi Arabia and Kuwait that support the spend and revenue hypothesis while United Arab Emirates results support fiscal neutrality. Furthermore, results also show one-way causality running from oil price to government expenditures only in case of Kuwait. The second objective of this study is to investigate the effect of oil price fluctuations on manufacturing output in Saudi Arabia, Kuwait and United Arab Emirates over the period of 1985-2017. The linear ARDL model results found that oil price negatively affected manufacturing output that leads to the evidence of symptoms Dutch Disease. The results of the non-linear model showed that negative oil price changes encourage and positive oil price discourage manufacturing output, but this impact is greater in the case of oil price decrease in these countries except United Arab Emirates. Furthermore, the results of granger causality shows oil price is granger cause of manufacturing output in all countries except United Arab Emirates. The third objective of this study is to investigate the effect of oil price on the trade balance in Saudi Arabia, Kuwait and United Arab Emirates over the period of 1980- 2017. The results of the linear ARDL model found that oil price positively affected total trade balance in all countries. The results of the nonlinear model showed that positive oil price encourage and negative oil price changes discourage trade balance, but this impact is greater in the case of oil price decrease in these countries except United Arab Emirates in the long run. Furthermore, the results of granger causality shows oil price is granger cause of trade balance only in case of Kuwait. The policy implications based on results are: First, the government understands the difference between positive and negative oil price changes as shown government expenditures are high when oil price increase. Secondly, policymakers understand nonlinear relationship of oil price with manufacturing sector to diversify the economy and escape from the Dutch Disease phenomenon and also formulate policy which can maintain a favorable environment to improve trade balance.